Il dolore degli altri - Pereira De Almeida, José Manuel (Rassegna di teologia, 2020)
Taking a cue from the work of Susan Sontag Regarding the Pain of the Other, we ask ourselves about the reality of the others in pain that we have before us. The others matter. The others are important to each of us. The presence of the other allows us to understand ourselves. When asked by the presence of the other, we are aware of our coexistence. Our personal responsibility translates into closeness in relationships with patients and the response to the pain of others can only be com-passion.